Kajian Koordinasi Sistem Proteksi Pada Sistem Transmisi 70 kV GI Banaran Kediri Transmission Line Bay Pare - Hafid Abibie; Sulistyowati; Ferdian Ronilaya (Elposys: Jurnal Sistem Kelistrikan, 2020)
The substation is one of the components in the electric power distribution system which plays a very important role because itis the connection between electricity services to customers. In the electric power distribution system, there are disturbances that often occur,one of which is a short circuit. For that, the way to overcome this is using the Distance Relay protection system, OCR / GFR and DEF. Thepurpose of writing this research is to determine the value of setting relay distance, setting Over Current Rele and Directional Earth Fault relayin order to secure the 70 kV transmission network connected to GI Banaran, which is then simulated using DigSILENT 15.1 software on thePare line by calculating symmetrical and asymmetrical disturbances. including 3-phase disturbance on February 1, 2018. The simulationresults show that the 3-phase disturbance occurs at Zone 1 relay distance of the Banaran Bay Pare substation with a trip time of 0.02 secondswith a fault impedance of 0.083 ohms below the relay impedance value of 0.887 ohms. The coordination between the distance relay on theside of the Banaran Bay Pare substation has worked well because there is no error reading the relay when it will cut off the disturbance.